2009
DOI: 10.1097/hjr.0b013e32832c8891
|View full text |Cite
|
Sign up to set email alerts
|

Prospective studies on the relationship between high-density lipoprotein cholesterol and cardiovascular risk: a systematic review

Abstract: Epidemiological studies have extensively evaluated the association between high-density lipoprotein cholesterol (HDL-C) and cardiovascular disease (CVD) risk. The objective of this systematic review was to enumerate the number of original prospective studies that showed a significant association between HDL-C and CVD risk and provided evidence of the consistency of this association across other lipid risk factors. A systematic MEDLINE literature search identified 53 prospective cohort and five nested case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 238 publications
(423 reference statements)
1
31
0
Order By: Relevance
“…However the amount of reduction beyond the effects of exercise had been inconsistent and numbers of controlled studies are few. HDL and LDL levels have been strongly associated with cardiovascular risk [41]. Even though no clear conclusions can be drawn on the beneficial effects of hypoxic training on HDL, it can be concluded that hypoxic training does not increase LDL levels, evident by none of the studies recording any significant increase in LDL levels.…”
Section: Cholesterol Levelsmentioning
confidence: 82%
“…However the amount of reduction beyond the effects of exercise had been inconsistent and numbers of controlled studies are few. HDL and LDL levels have been strongly associated with cardiovascular risk [41]. Even though no clear conclusions can be drawn on the beneficial effects of hypoxic training on HDL, it can be concluded that hypoxic training does not increase LDL levels, evident by none of the studies recording any significant increase in LDL levels.…”
Section: Cholesterol Levelsmentioning
confidence: 82%
“…Dyslipidaemia in obesity and OSA Obesity, MetS and type-II diabetes are characterised by a specific pattern of plasma lipids, called atherogenic dyslipidaemia [249], which is a powerful cardiovascular risk factor [250][251][252]. Atherogenic dyslipidaemia is also common in OSA, and a role for OSA in worsening dyslipidaemia is suggested by several experimental and clinical studies.…”
Section: Intermittent Hypoxia In Animal Modelsmentioning
confidence: 99%
“…Most laboratory covariates were included, a priori, as continuous variables rather than as risk thresholds because of the expanding literature that now suggests there are no safe cut-offs for risk factors and that increases and decreases in covariates at any level are associated with increased or decreased cardiovascular risk [17][18][19][20] Furthermore, modern computing facilities and web-based tools reduce the need for simple computational algorithms or scoring systems [21].…”
Section: Statistical Analysesmentioning
confidence: 99%